Hyperactive behaviour and academic achievements in a sample of foundation phase learners - Pokroy, Raylene (My University, 2014)
This study examined the role that Attention Deficit Hyperactivity Disorder (ADHD) placed in the academic achievement of a sample o f black foundation phase learners in an inner city school in the Johannesburg area. The ADHD Rating Scale (DuPaul, 1991) was used to diagnose ADHD in the sample. The Rating scale distinguished between the subtypes o f ADHD outlined in the DSM-IV: ADHD - Predominantly Inattentive type (primarily with symptoms of inattention) and ADHD - Predominantly Hyperactive- Impulsive type (primarily with symptoms of hyperactivity). Academic achievement was established from the profiles of the learners’ school results. Learners in grades 1 and 2 were graded on a 5-point scale according to the school’s grading system. This research found a significant relationship between ADHD scores and academic achievement and failure rates of Black South African children- The number of learners who are failing, as well as who have significantly high scores of ADHD was highly significant (p=0.0010). This points to a possible universality with regard to ADHD and its impact on academic achievement. Therefore ADHD may play a significant role in the school success or failure of Black children in the country.